UMPSA and NIT Yonago College strengthen relations through Edu-Tourism Summer Programme 2024 - Muhammad Zufli, Zuhari (UMPSA, 2024)
KUALA LUMPUR, 10 September 2024 – A total of 11 students accompanied by Professor Morita Shiota from the National Institute of Technology (NIT), Yonago College, Japan, participated in the Edu-Tourism Summer Programme 2024 organised by the Centre for International Relations (CIR), UMPSA, from 4 to 10 September 4 2024.